A Secure Decentralized E Voting With Blockchain and Smart Contracts (International Journal of Scientific Research in Science and Technology, 2025)
A democratic election is a crucial act in each nation, as it determines the country's future for a specific term. Some of the older voting methods, such as Ballot Paper and EVM (Electronic Voting Machine), have disadvantages such as lack of transparency, poor voter turnout, vote rigging, and many others. Using Blockchain technology and Smart Contracts, it is simple to circumvent the flaws of the Ballot system and EVM. Electronic Voting Powered by Blockchain and Smart Contracts outperforms these antiquated voting methods by delivering secure results in less time and at a lower cost. With E-Voting utilizing Blockchain, prices can be lowered, the necessity for Polling stations and the consumption of resources such as EVMs and Ballot Papers may be decreased, and security can be improved by offering End-to-End Encryption and authenticity. This blockchain-powered e-voting can readily acquire trust due to the transaction's transparency, immutability, and difficulty of modification once hosted, as a result of smart contracts. Using OTP Verification and face verification, the suggested solution is a MERN-based web application with a multitude of upgraded authentication and permission techniques. To improve security, this voting data is saved as a transaction in a Blockchain-based distributed ledger using smart contracts.
Keywords: Blockchain; authenticity; Verification; stations